The Use of Digital Media “Quiziz” in the Learning Process in Elementary Schools - Alfaqir, Paras; Jefri; Firdaus, Husein; Hidayat, Wahyu; Rizqa, Miftahir (Episteme: Jurnal Kajian Mahasiswa, 2025)
The development of digital technology has brought significant changes to the field of education, especially in the learning process at the elementary school level. One of the most widely used digital media is Quizizz, an interactive and enjoyable game-based learning platform. This study aims to describe the use of the digital medium Quizizz in the learning process at elementary schools and to analyze its impact on students’ motivation and learning outcomes. The research method used is descriptive qualitative, with data collected through library research. The results show that the use of Quizizz can enhance students’ active participation, strengthen their understanding of the material, and create a more engaging and competitive learning atmosphere. In addition, teachers find it helpful for conducting learning evaluations quickly and accurately. Therefore, the digital medium Quizizz can serve as an innovative alternative in 21st-century learning that supports the creation of active, creative, and enjoyable learning in elementary schools.